BIOCHEMICAL AND HORMONAL PROFILE OF THE AMNIOTIC FLUID FROM NELORE CALVES CONCEIVED BY DIFFERENT REPRODUCTION BIOTECHNOLOGIES - Piagentini, Marcelo; Prestes, Nereu Carlos; Fredrichsen Moya-Araujo, Carla; Marques Araujo, Gustavo Henrique; Kiomi Takahira, Regina; Oba, Eunice (Revista Acadêmica Ciência Animal, 2012)
This study aimed to quantify biochemical constituents and hormonal concentrations in the amniotic fluid of Nelore calves conceived by different reproduction biotechnologies. Sixty animals were used and divided into: 1 – Twenty Nelore cows pregnant of calves obtained by artificial insemination; 2 – Twenty cows pregnant with Nelore calves obtained by embryo transference; 3 – Twenty cows pregnant with Nelore calves obtained by in vitro production. During the expulsion phase, the amnion was punctured and 15 mL of fluid were collected. The biochemical evaluation was performed with commercial kits in accordance to the manufacturer’s recommendations. It was used the radioimmunoassay to assess the progesterone and testosterone levels. The statistical analysis used was the variance analysis and Tukey (5% significance level). Mean urea and creatinine when comparing the three groups showed that group 3 had higher values of these two metabolites, suggesting that the kidney maturity is suitable. For gamma-glutamyltransferase, group 3 had a lower value compared to group 1. This enzyme is related to metabolism, may be inferred that the metabolic activity is high in animal production in vitro. The glucose values did not differ between the groups, suggests that the maternal-fetal exchanges were suitable for the power supply to the fetus. Lower chloride concentration was showed in group 3. Sodium and potassium were found in greater quantities in group 3 when compared to other groups. There was no significant difference for the testosterone and progesterone. The results obtained in biochemical analysis can conclude that the renal and liver activity and maternal-fetal exchange are normal in the different groups.